EXPLORING INTERACTIVITY AND ENGAGEMENT: IMPROVING WRITING SKILLS WITH CHATGPT FOR FUN LEARNING - Hidayatullah, Efendi (Journal of Language, Literature and Teaching, 2023)
This study examines the potential benefits of utilizing ChatGPT in the teaching and learning process. ChatGPT is an advanced language model that aims to improve writing skills through customized, fun learning based on needs assessment and a planned curriculum. The research explores how ChatGPT can make learning to write more enjoyable, given the increasing need for effective and enjoyable learning tools characterised by the development of technology in education. The study employs a mixed methods approach, utilising both quantitative analysis and qualitative feedback collection. Quantitative data will be gathered by assessing writing skills before and after the intervention. In contrast, the study will collect qualitative data through surveys and interviews to gain a deeper understanding of the participants. The participants of this study are teachers and grade XI students of SMK Muhammadiyah Mertoyudan who used ChatGPT for writing activities for two months. The evaluation methods used in this study include teacher assessment, written tests, and qualitative analysis. Additionally, an assessment rubric was used for the on-writing evaluation. The research findings indicate that, apart from ChatGPT, students are also accustomed to using Bing AI to explore interactivity and engagement in writing skills. The study suggests that integrating ChatGPT into writing practice can increase engagement and interactivity. These findings can help teachers and students integrate machine learning in a good and ethical way.